High thermal conductivity and high strength magnesium alloy and preparation method thereof
By introducing a medium-temperature slow and medium deformation process before the high temperature is severely plastic deformation, the problem of poor strength of magnesium alloy is solved, and the comprehensive performance improvement of high thermal conductivity and high strength is achieved. It is suitable for electronic components with high heat dissipation needs.
Patent Information
- Application Number
- CN202410158839.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-04
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-02-04
AI Technical Summary
The strength of existing high-thermal conductivity magnesium alloys is poor, making it difficult to meet the simultaneous demand of high thermal conductivity and high strength of heat dissipation structural parts.
A composite deformation process is adopted, which is first performed at a moderate temperature and moderate deformation to precipitate solid solution atoms, and then undergoes rapid and violent deformation at a high temperature to promote dynamic recrystallization and grain refinement.
The thermal conductivity and strength of magnesium alloys have been significantly improved. The room temperature thermal conductivity of the prepared high-thermal conductivity and high-strength magnesium alloys reaches 143~151W/(m·K), and the yield strength is 355~370MPa, meeting the heat dissipation needs in 5G communications, electronics 3C, new energy vehicles and other fields.
Smart Images

Figure CN117987752B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal materials, and in particular to a high-thermal-conductivity and high-strength magnesium alloy and a preparation method thereof. Background Art
[0002] With the advancement of science and technology, various electronic components are developing towards high integration, which puts forward higher requirements on the heat dissipation capacity of materials. Magnesium alloy is light in weight (density ≈ 1.74g / cm 3 ) and high specific strength, and has higher thermal conductivity than other lightweight materials (plastics, ceramics). Therefore, in the context of energy conservation, emission reduction and lightweighting, magnesium alloys have great application potential as lightweight and high-strength heat dissipation materials.
[0003] At present, the most common method for designing high thermal conductivity magnesium alloys is to reduce the content of solid solution atoms in the matrix to alleviate lattice distortion and reduce the scattering of electrons and phonons when transferring heat, thereby achieving high thermal conductivity. However, the solid solution strengthening effect of low solid solubility alloys is very limited, resulting in generally low strength, which limits their wide application in the field of heat dissipation structural parts.
[0004] A Chinese patent (publication number CN 109136700 A) discloses a Mg-RE-Al alloy used in inverter housings, with a thermal conductivity of 94 to 97 W / (m·K), but its yield strength is less than 160 MPa. As a high thermal conductivity magnesium alloy, its strength still needs to be improved to enhance its application scenarios.
[0005] In order to solve the problem of poor strength of high thermal conductivity magnesium alloys, the introduction of plastic deformation process can be considered. It is generally believed that after severe deformation, the grains of magnesium alloys are significantly refined and the strength is greatly improved; however, the high-density dislocations and high-strength textures introduced by severe deformation have an adverse effect on thermal conductivity. For example, the Mg-(0.5-5.0%)Zn (reference 1: Journal of Alloys and Compounds 621 (2015) 250-255) and Mg-(0.5, 0.9, 1.5%)Al binary alloys (reference 2 Journal of Alloys and Compounds 608 (2014) 19-24) reported in the literature have lower thermal conductivity after extrusion than the corresponding cast alloys. Therefore, it is urgent to design a composite deformation process to improve the comprehensive performance of high thermal conductivity and high strength magnesium alloys. Summary of the invention
[0006] In view of this, an object of the present invention is to provide a high thermal conductivity and high strength magnesium alloy and a preparation method thereof.
[0007] The purpose of the present invention is to solve the problem that it is difficult to prepare high-strength and high-thermal conductivity magnesium alloys in the prior art. Mg-RE-Al alloy with high strength and thermal conductivity and excellent processing performance is selected as the base alloy, and a deformation process for simultaneously improving thermal conductivity and strength is proposed, which has important engineering value.
[0008] The technical solution of the present invention is as follows:
[0009] A method for preparing a high thermal conductivity and high strength magnesium alloy comprises the following steps:
[0010] S1, processing the magnesium alloy ingot into a cylindrical billet and preheating it;
[0011] S2, subjecting the blank preheated in step S1 to a first deformation treatment, cooling, and obtaining a deformed blank; the deformation temperature is 300-350°C; the deformation amount is 20%-40%, and the deformation rate is 0.1-2 mm / s.
[0012] S3, processing the deformed blank into a cylindrical blank and keeping it warm for a period of time;
[0013] S4. Performing a second deformation process on the columnar blank, cooling, and water quenching to obtain the high thermal conductivity and high strength magnesium alloy.
[0014] The magnesium alloy is Mg-RE-Al.
[0015] The RE includes at least one of Sm, Ce, and La.
[0016] In step S1, the preheating treatment temperature is 300-350°C, and the preheating time is 30-60 minutes.
[0017] In step S3, the insulation temperature is 350-400° C. and the insulation time is 60-90 min.
[0018] In step S4, the second deformation temperature is 350-400°C.
[0019] In step S4, the second deformation amount is 50% to 75%, and the deformation rate is 5 to 10 mm / s.
[0020] The high thermal conductivity and high strength magnesium alloy prepared by the preparation method also falls within the protection scope of the present invention.
[0021] The application of the high thermal conductivity and high strength magnesium alloy in the field of heat dissipation structural parts also falls within the protection scope of the present invention.
[0022] The key points of the present invention are:
[0023] The Al atoms dissolved in the Mg-RE-Al alloy are easily combined with RE atoms to form Al-RE strengthening phases, which consume the solute atoms in the matrix, so it has a higher thermal conductivity, but poor strength performance. The present invention is aimed at the Mg-RE-Al alloy, and firstly performs slow and moderate deformation at medium temperature to precipitate the solute atoms to the maximum extent, greatly improve the thermal conductivity, and promote dynamic recrystallization during the subsequent high-temperature rapid and drastic deformation. Through comparative studies, the present invention finds that: ① Medium-temperature deformation can provide a certain driving force to precipitate RE and Al atoms and avoid cracking during the deformation process, thereby ensuring processing reliability; at the same time, it avoids the increase of RE and Al element solubility due to excessively high temperature, which has an adverse effect on thermal conductivity. ② The purpose of slow deformation is to allow RE and Al atoms to have sufficient time to precipitate, which is more conducive to improving thermal conductivity than rapid deformation. ③ Moderate deformation is to avoid introducing too high dislocation density and texture strength, which will damage thermal conductivity; at the same time, it avoids cracking during alloy deformation. ④ In addition, a large number of Al-RE particle phases can be precipitated as heterogeneous nucleation points during the slow deformation process, and a large amount of distortion energy can be stored, thereby effectively promoting dynamic recrystallization during the subsequent deformation process, making the grain refinement effect significant. In summary, the present invention controls the deformation temperature to 300-350°C; the deformation rate to 0.1-2 mm / s; and the deformation amount to 20%-40%.
[0024] The second deformation adopts high temperature, rapid and violent deformation to greatly improve the strength. The present invention further found through comparative research that in the second deformation: ① High temperature can provide sufficient power to promote dynamic recrystallization of deformed grains, increase the recrystallization ratio, refine the grains and weaken the texture. It is beneficial to improve thermal conductivity and strength. ② Rapid deformation is used to shorten the deformation time so that the recrystallized grains have no time to grow, avoiding adverse effects on strength. ③ The use of violent deformation can effectively refine the grains, produce high-density dislocations and precipitate a large number of nano-sized second phases, so that the grain boundary strengthening, dislocation strengthening and precipitation strengthening effects are enhanced. Under the combined effect of these strengthening mechanisms, the strength is greatly improved. In summary, the present invention controls the deformation temperature to 350-400℃; the deformation rate to 5-10mm / s; the deformation amount to 50%-75%.
[0025] The beneficial technical effects of the present invention are as follows:
[0026] 1. In the prior art, it is often believed that magnesium alloys have significant grain refinement and greatly improved strength after severe deformation, so temperature changes are often used; however, the high-density dislocations and high-strength textures introduced by severe deformation have an adverse effect on thermal conductivity, and cannot be applied to 5G communications, electronic 3C, new energy vehicles and other fields that have high requirements for heat dissipation; the present invention introduces a low-temperature slow and moderate deformation process before high-temperature severe plastic deformation to induce the precipitation of solid solution atoms to the greatest extent, greatly improve thermal conductivity, and significantly refine grains; synergistically improve the thermal conductivity and strength of magnesium alloys, and obtain a high thermal conductivity and high-strength deformed magnesium alloy with excellent comprehensive performance. The room temperature thermal conductivity of the deformed magnesium alloy prepared by the present invention is 143~151W / (m·K), the yield strength is 355~370MPa, the tensile strength is 398~425MPa, and the elongation is 14~17%. It can effectively meet the heat dissipation requirements of components such as 5G communications, electronic 3C, and new energy vehicles, and has a strong application prospect.
[0027] 2. The alloy system of the present invention is preferably Mg-RE-Al, which has excellent casting properties relative to common magnesium alloys, such as Mg-Mn alloys, mainly due to the purification effect of the RE element on the Mg alloy melt. At the same time, compared with the Mg-Mn alloy, the grain size of the Mg-RE-Al alloy is finer, and it contains a large amount of fine and dispersed Al-RE second phase, so it has higher high temperature resistance and toughness. In addition, compared with Mn, Al and Mg have similar atomic volumes and are easy to react with RE to form a second phase, so the addition of Al has little effect on thermal conductivity; the two-pass deformation process designed by the present invention can also well promote the precipitation of solute atoms, thereby maximizing thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0029] Figure 1 This is the room temperature tensile curve of the extruded alloy of Example 1 (Mg-4Sm-2Al);
[0030] Figure 2 The metallographic structure of the as-cast alloy of Example 1 (Mg-4Sm-2Al);
[0031] Figure 3 This is the electron backscatter diffraction pattern of the wrought alloy of Example 1 (Mg-4Sm-2Al);
[0032] Figure 4 This is the electron backscattered diffraction pattern of the extruded alloy of Example 1 (Mg-4Sm-2Al);
[0033] Figure 5Schematic diagram of the processing flow of each step of the alloy in Example 1 (Mg-4Sm-2Al). DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0035] Example 1
[0036] The Mg-RE-Al alloy selected in this embodiment is Mg-4Sm-2Al, with a thermal conductivity of 107W / (m·K) in the cast state, a yield strength of 102MPa, and excellent machinability. The first deformation process adopts a forging process, and the second deformation process adopts a hot extrusion process. The specific process is shown in the following detailed steps:
[0037] Step 1: Preheating:
[0038] The Mg-4Sm-2Al alloy ingot is subjected to preheating after removing the surface oxide film, turning into a cylindrical billet, and performing preheating; the cylindrical billet has a height of 100 mm and a diameter of 60 mm; the preheating temperature is 350° C. and the time is 60 min;
[0039] Step 2: Forging deformation:
[0040] The preheated cylindrical billet obtained in step 1 is placed in a heating furnace at 350°C for 1 hour. Then it is pressed down by a horizontal forging press with a pressing deformation of 40%, a deformation rate of 0.5 mm / s, and a deformation temperature of 350°C to obtain a forged round ingot.
[0041] Step 3: Insulation treatment:
[0042] The forged ingot obtained in step 2 is turned horizontally into a cylindrical billet with a diameter of 60 mm and a height of 40 mm; the billet is placed in a heat treatment furnace, heated to 350° C. and kept warm for 60 minutes; and an extruded billet is obtained.
[0043] Step 4: Hot extrusion:
[0044] The extruded billet obtained in step 3 was placed in a horizontal extruder die and extruded into a round rod with a diameter of 12 mm; the heating temperature inside the extrusion die was set to 375°C, and the extrusion ratio and extrusion speed were set to 25:1 and 5 mm / s respectively. After extrusion deformation, the deformed Mg-4Sm-2Al alloy was obtained by water quenching.
[0045] Figure 1This is the room temperature tensile curve of the deformed alloy in Example 1.
[0046] Figure 2 This is a metallographic photograph of the cast Mg-4Sm-2Al alloy in Example 1. It can be found that the microstructure of the cast Mg-4Sm-2Al alloy is mainly composed of α-Mg matrix and eutectic structure. The rod-like phase with typical eutectic morphology is Al 11 Sm3 phase, and there are also a small amount of Al2Sm phase particles inside the grains.
[0047] Figure 3 This is the EBSD image of the Mg-4Sm-2Al alloy (forged state) obtained in step 2 of Example 1. It can be seen that the grains are significantly refined after forging, the average grain size is 29.2 μm, and the maximum texture strength is 18.1.
[0048] Figure 4 This is the EBSD image of the Mg-4Sm-2Al alloy (extruded state) obtained in step 4 of Example 1. The grains are further refined to 2.2 μm, the grain boundary strengthening effect is greatly enhanced, and the strength of the alloy is improved. At the same time, the Al in the alloy after extrusion 11 The Sm3 phase is broken into fine particles, the strengthening effect of the second phase is increased, and the strength is improved. In addition, a large number of deformed grains undergo dynamic recrystallization during the hot extrusion process. Compared with the deformed grains, the recrystallized grains show a more uniform random orientation, which weakens the texture and reduces the maximum texture strength to 6.9, which is beneficial to thermal conductivity.
[0049] Figure 5 This is a schematic diagram of the processing flow of Example 1, in which the Mg-4Sm-2Al alloy is prepared from the cast state through forging, turning and hot extrusion to obtain the final deformed alloy.
[0050] Example 2
[0051] The difference between this embodiment and embodiment 1 lies in that the alloy composition and the specific deformation process are different.
[0052] The composition of the Mg-RE-Al alloy selected in this embodiment is Mg-4Gd-4Al, the thermal conductivity in the cast state is 102 W / (m·K), and the yield strength is 125 MPa.
[0053] The deformation process in step 4 is as follows: the extruded billet obtained in step 3 is placed into a horizontal extruder die and extruded into a round rod with a diameter of 15 mm; the heating temperature inside the extrusion die is set to 350° C., and the extrusion ratio and extrusion speed are set to 16:1 and 8 mm / s respectively.
[0054] The remaining steps are the same as those in Example 1.
[0055] Example 3
[0056] The difference between this embodiment and embodiment 1 lies in that the alloy composition and the specific deformation process are different.
[0057] The composition of the Mg-RE-Al alloy selected in this embodiment is Mg-6La-4Al, the thermal conductivity in the cast state is 110 W / (m·K), and the yield strength is 91 MPa.
[0058] The deformation process in step 4 is as follows: the extruded billet obtained in step 3 is placed into a horizontal extruder die and extruded into a round rod with a diameter of 20 mm; the heating temperature inside the extrusion die is set to 350° C., and the extrusion ratio and extrusion speed are set to 9:1 and 8 mm / s respectively.
[0059] The remaining steps are the same as those in Example 1.
[0060] Comparative Example 1
[0061] The difference between this comparative example and Example 1 is that the deformation rate of the forging process in step 2 is 4 mm / s, and the remaining steps are the same as those in Example 1.
[0062] Comparative Example 2
[0063] The difference between this comparative example and Example 1 is that the deformation temperature of the forging treatment in step 2 is 450° C., and the remaining steps are the same as those in Example 1.
[0064] Comparative Example 3
[0065] The difference between this comparative example and Example 1 is that the deformation amount of the forging process in step 2 is 15%, and the remaining steps are the same as those in Example 1.
[0066] Comparative Example 4
[0067] The difference between this comparative example and Example 1 is that the deformation rate of hot extrusion in step 4 is 20 mm / s, and the remaining steps are the same as Example 1.
[0068] Comparative Example 5
[0069] The difference between this comparative example and Example 1 is that the deformation temperature of hot extrusion in step 4 is 500° C., and the remaining steps are the same as those in Example 1.
[0070] Comparative Example 6
[0071] The difference between this comparative example and Example 1 is that the extrusion ratio of hot extrusion in step 4 is 4:1, and the remaining steps are the same as Example 1.
[0072] Comparative Example 7
[0073] The difference between this comparative example and Example 1 is that only steps 1 and 2 of preheating and forging deformation are performed, while steps 3 and 4 of heat preservation and hot extrusion are not performed.
[0074] Comparative Example 8
[0075] The difference between this comparative example and Example 1 is that only the heat preservation and hot extrusion of steps 3 and 4 are performed, while the preheating and forging deformation of steps 1 and 2 are not performed.
[0076] Comparative Example 9
[0077] The difference between this comparative example and Example 1 is that the alloy system is replaced with Mg-4Ce-2Mn, and the remaining steps are the same as Example 1.
[0078] Performance Testing
[0079] The mechanical properties of the composites prepared in Examples 1-3 and Comparative Examples 1-8 were tested in the following manner:
[0080] Thermal conductivity W / (m·K): GB / T 10294-2008
[0081] Yield strength (MPa): GB / T228.1-2010
[0082] Tensile strength (MPa): GB / T228.1-2010
[0083] Elongation (%): GB / T228.1-2010
[0084] Table 1 Test results of thermal conductivity and mechanical properties of high thermal conductivity and high strength deformed Mg-4Sm-2Al alloy
[0085]
[0086]
[0087] The thermal conductivity of the Mg-4Sm-2Al extruded alloy obtained in Example 1 is 143 W / (m·K), the yield strength is 370 MPa, the tensile strength is 425 MPa, and the elongation is 17%.
[0088] The comprehensive properties of the deformed Mg-4Gd-4Al alloy prepared in Example 2 are as follows: thermal conductivity is 145 W / (m·K), yield strength is 361 MPa, tensile strength is 403 MPa, and elongation is 14%.
[0089] The comprehensive properties of the deformed Mg-6La-4Al alloy prepared in Example 3 are as follows: thermal conductivity is 151 W / (m·K), yield strength is 355 MPa, tensile strength is 398 MPa, and elongation is 15%.
[0090] The comprehensive properties of the deformed Mg-4Sm-2Al alloy prepared in Comparative Example 1 are as follows: thermal conductivity is 129W / (m·K), yield strength is 312MPa, tensile strength is 366MPa, and elongation is 10%. Compared with Example 1, the thermal conductivity and strength of Comparative Example 1 are lower than those of Example 1. This is mainly due to the fact that the forging deformation rate of the alloy in Comparative Example 1 is too fast, the precipitation process lasts for a short time, and the decrease in the solute atom content is smaller, resulting in a less obvious improvement in thermal conductivity relative to Example 1. On the other hand, due to the reduction in the number of Al2Sm precipitated phases, the number of particle phase nucleation points is reduced, resulting in a reduction in the dynamic recrystallization ratio, and the final strength is lower than that of Example 1.
[0091] The comprehensive properties of the deformed Mg-4Sm-2Al alloy prepared in Comparative Example 2 are as follows: thermal conductivity is 120W / (m·K), yield strength is 336MPa, tensile strength is 379MPa, and elongation is 15%. Compared with Example 1, the thermal conductivity of Comparative Example 2 is significantly lower than that of Example 1, while the strength is similar. This is mainly because the solubility of Sm and Al in the alloy of Comparative Example 2 increases with increasing temperature, and more alloy elements are dissolved into the matrix rather than precipitated, resulting in only a small increase in thermal conductivity.
[0092] The comprehensive properties of the deformed Mg-4Sm-2Al alloy prepared in Comparative Example 3 are as follows: thermal conductivity is 133W / (m·K), yield strength is 318MPa, tensile strength is 360MPa, and elongation is 12%. Compared with Example 1, the thermal conductivity and strength of Comparative Example 3 are lower than those of Example 1. This is mainly because the forging deformation of the alloy in Comparative Example 3 is too small, which weakens the dynamic precipitation effect and reduces the improvement of thermal conductivity. In addition, too small a deformation will also reduce the distortion storage energy, reduce the dynamic recrystallization power during hot extrusion, reduce the grain refinement effect, and affect the strength.
[0093] The comprehensive properties of the deformed Mg-4Sm-2Al alloy prepared in Comparative Example 4 are as follows: thermal conductivity is 138W / (m·K), yield strength is 315MPa, tensile strength is 355MPa, and elongation is 9%. Compared with Example 1, the strength of Comparative Example 4 is lower than that of Example 1, while the thermal conductivity is similar. This is mainly because the grains do not have enough time for dynamic recrystallization under the too fast extrusion rate, resulting in coarse grains after extrusion, reduced grain boundary strengthening effect and affected strength.
[0094] The comprehensive properties of the deformed Mg-4Sm-2Al alloy prepared in Comparative Example 5 are as follows: thermal conductivity is 128W / (m·K), yield strength is 340MPa, tensile strength is 386MPa, and elongation is 15%. Compared with Example 1, the thermal conductivity and strength of Comparative Example 5 are lower than those of Example 1. The main reason is that high temperature increases the solubility of alloy elements and promotes the growth of grains, which reduces the improvement of thermal conductivity and strength.
[0095] The comprehensive properties of the deformed Mg-4Sm-2Al alloy prepared in Comparative Example 6 are as follows: thermal conductivity is 137W / (m·K), yield strength is 302MPa, tensile strength is 351MPa, and elongation is 12%. Compared with Example 1, the strength of Comparative Example 6 is lower than that of Example 1, and the thermal conductivity is similar. Too small a deformation amount will reduce the dynamic recrystallization ratio, weaken the grain boundary strengthening effect, and result in a limited increase in strength.
[0096] The comprehensive properties of the deformed Mg-4Sm-2Al alloy prepared in Comparative Example 7 are as follows: thermal conductivity is 139W / (m·K), yield strength is 188MPa, tensile strength is 242MPa, and elongation is 6%. The dynamic precipitation effect is obvious during the forging deformation process, which is the main stage for reducing the solute atom content and improving the thermal conductivity. Hot extrusion can sharply reduce the grain size by about an order of magnitude, greatly enhancing the grain boundary strengthening effect, and is the main stage for improving the strength. Therefore, the thermal conductivity of Comparative Example 7, which only undergoes forging deformation, is close to that of Example 1, while the strength is significantly lower than that of Example 1.
[0097] The comprehensive properties of the deformed Mg-4Sm-2Al alloy prepared in Comparative Example 8 are as follows: thermal conductivity is 113W / (m·K), yield strength is 278MPa, tensile strength is 323MPa, and elongation is 10%. This comparative example is directly subjected to high-temperature rapid hot extrusion by the cast alloy. The solubility of the alloy elements is high and there is no time for precipitation, so the thermal conductivity is improved very little. In addition, due to the lack of the first forging deformation to provide a driving force for dynamic recrystallization during the hot extrusion process, the grain size is increased compared to Example 1, and the strength improvement is also reduced.
[0098] The comprehensive properties of the deformed Mg-4Ce-2Mn alloy prepared in Comparative Example 9 are as follows: thermal conductivity is 114W / (m·K), yield strength is 296MPa, tensile strength is 324MPa, and elongation is 8%. In this comparative example, the Al element is replaced by Mn, and the lattice distortion caused by the formation of substitutional solid solution is much greater than that of Al, which greatly reduces the thermal conductivity. At the same time, the solid solubility of Mn is low, the solid solution strengthening effect is limited, and the grains are coarse, resulting in a decrease in strength.
[0099] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a high thermal conductivity and high strength magnesium alloy, characterized in that: The following steps are involved: S1, processing the magnesium alloy ingot into a cylindrical billet and preheating it; S2, subjecting the blank subjected to the preheating treatment in step S1 to a first deformation treatment, cooling, and obtaining a deformed blank; the first deformation treatment: the deformation temperature is 300-350°C, the deformation amount is 20%-40%, and the deformation rate is 0.1-2 mm / s; S3, processing the deformed blank into a cylindrical blank and keeping it warm for a period of time; S4, performing a second deformation process on the cylindrical blank and water quenching to obtain the high thermal conductivity and high strength magnesium alloy; The second deformation temperature is 350~400℃; The magnesium alloy composition is one of Mg-4Sm-2Al, Mg-4Gd-4Al, and Mg-6La-4Al; When the magnesium alloy composition is Mg-4Sm-2Al, step S4 specifically comprises: placing the cylindrical billet of step S3 into an extruder die and extruding it into a round rod with a diameter of 12 mm, with an extrusion ratio and an extrusion speed of 25:1 and 5 mm / s respectively; and water quenching after extrusion deformation to obtain the high thermal conductivity and high strength magnesium alloy; When the magnesium alloy composition is Mg-4Gd-4Al, step S4 is specifically: putting the cylindrical billet of step S3 into an extruder die and extruding it into a round rod with a diameter of 15 mm; the extrusion ratio and the extrusion speed are 16:1 and 8 mm / s respectively; and obtaining the high thermal conductivity and high strength magnesium alloy; When the magnesium alloy composition is Mg-6La-4Al, step S4 is specifically: putting the cylindrical billet of step S3 into an extruder die and extruding it into a round rod with a diameter of 20 mm; the extrusion ratio and the extrusion speed are 9:1 and 8 mm / s respectively; and obtaining the high thermal conductivity and high strength magnesium alloy.
2. The preparation method according to claim 1, characterized in that: In step S1, the preheating temperature is 300-350°C, and the preheating time is 30-60 min.
3. The preparation method according to claim 1, characterized in that: In step S3, the holding temperature is 350-400° C., and the holding time is 60-90 min.
4. A high thermal conductivity and high strength magnesium alloy prepared by the preparation method according to any one of claims 1 to 3.
5. Application of the high thermal conductivity and high strength magnesium alloy as claimed in claim 4 in the field of heat dissipation structural parts.
Citation Information
Patent Citations
High-thermal-conductivity magnesium alloy, inverter shell, inverter and automobile
CN109136700A
High-performance magnesium alloy tube for automobile bumper bars and manufacturing method thereof
CN104313440A